2020
DOI: 10.1016/j.bpj.2019.11.2019
|View full text |Cite
|
Sign up to set email alerts
|

Tau Differentially Regulates the Dynamic Localization of Early Endosomes and Lysosomes

Abstract: Endogenous electric fields are present in many biological processes including at the edge of healing wounds and can direct cell migration. Here we measure the effect of DC electric fields on actin polymerization dynamics. We find that actin waves are guided by DC electric fields for multiple cell types. Giant Dictyostelium discoideum cells (produced via electrofusion) allow us to measure electric field response of actin waves located far from the leading or trailing edge of a cell, and thus decouple cell polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Microtubule‐associated proteins including Tau are a key component of these regulatory networks. Aberrant Tau phosphorylation can disrupt the targeting of critical cargoes to their specific destinations [66]. Recently, it has been reported that patients with rpAD contain ~80% misfolded four‐repeat Tau (4R‐Tau) and ~20% of misfolded 3R‐Tau isoform with similar conformations [11].…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule‐associated proteins including Tau are a key component of these regulatory networks. Aberrant Tau phosphorylation can disrupt the targeting of critical cargoes to their specific destinations [66]. Recently, it has been reported that patients with rpAD contain ~80% misfolded four‐repeat Tau (4R‐Tau) and ~20% of misfolded 3R‐Tau isoform with similar conformations [11].…”
Section: Discussionmentioning
confidence: 99%